Beauté Congo : 1926 - 2015 - Magnin, André; Bofane, In Koli Jean; Bayet, Thomas; Deplaen, Michael; Malaquais, Dominique (Parijs : Fondation Cartier, 2015)
Lubaki, Albert ; Lubaki, Antoinette ; Djilatendo ; Mampinda, Paul ; Ngoma ; Bela ; Bya ; Grégory ; Ilunga, Norbert ; Kabeya ; Kayembe ; Kalela, Raphaël ; Kilima, Oscar ; Lukanga ; Mulongoy, Pilipili ; Mwena ; N'Kulu ; Yumba ; Kibwanga, Mwenze ; Kaballa, Sylvestre ; Kamba, Jean Bosco ; Muntu, Mode ; Moke ; Samba, Chéri ; Ledy, Cheik ; Bodo, Pierre ; Chérin, Chéri ; Shula, Monsengo ; Mika, JP ; Mingiedi Tunga, Mega ; Shomali, Kura ; Tshindele, Pathy ; Bandoma, Steve ; Kingeleze, Body Isek ; Nimi, Rigobert ; Mfumu'eto, Papa ; Deapa, Jean ; Studio 3Z ; Katembo, Kiripi ; Baloji, Sammy
Catalogus naar aanleiding van de tentoonstelling Beauté Congo, Parijs, Fondation Cartier, van 11 juli 2015 tot 10 januari 2016.
boek